In the Long Run: Physical Activity in Early Life and Cognitive Aging - Greene, Charlotte; Lee, Hyunah; Thuret, Sandrine (Frontiers in Neuroscience, 2019)
A certain degree of age-related cognitive decline is normal; however, some people retain more cognitive function than others. Cognitive impairment is associated with an increased risk of dementia. Thus, understanding the factors that contribute to cognitive reserve is crucial, so effective strategies for the prevention of dementia can be developed. Engaging in physical activity can delay cognitive decline and reduce the risk of dementia and a number of early life conditions have been shown to have long-lasting effects on cognition. This mini-review combines these two observations to evaluate the evidence from both animal models and epidemiological studies for physical activity in early life (≤ 30 years) delaying cognitive decline in later life (cognition tested ≥ 60 years). Three epidemiological studies were found; two showed a positive association and one found none. The latter was deemed to have an unreliable method. A review of animal studies found none that analysed the effect of physical activity in early life on cognition in later life. However, in rodent models that analysed mid-life cognition, runners showed improved cognition and enhanced adult hippocampal neurogenesis, changes which were preserved across the life span. Currently, there is insufficient evidence to conclude whether physical activity in early life may delay cognitive decline in later life, but these results indicate that further studies are warranted. Future human research should be in the form of longitudinal studies that begin below ≤ 15 years and assess sex differences. Crucially, the physical activity data must define type, quantity and intensity of exercise.